Síntese e aplicação de organocatalisadores em reações de epoxidação assimétricas visando a síntese de compostos bioativos - Deobald, Anna Maria (Universidade Federal de São Carlos, 2013)
Given the importance and growth of organocatalysis as an important tool in organic synthesis, in this work a new class of organocatalysts derived from proline was synthesized and applied in epoxidation reactions of electron deficient conjugated double bonds. Additionally, the methodology was employed in the synthesis of bioactive compounds. Initially, the new organocatalysts were prepared as shown in the scheme below. They were synthesized from proline, an inexpensive and commercially available amino acid, in two or three steps with good overall yields. The organocatalysts 1a-e were employed in the epoxidation of α,β-unsaturated aldehydes. The best results were obtained with catalyst 1d, furnishing the epoxy-aldehydes 4a-h in good yields, diastereoisomeric ratio and enantiomeric excesses. It is worthy to note that this methodology could employ mild conditions and environmental friendly solvents (water and ethanol). The amino-alcohols 2a-e were used as catalysts in the epoxidation of chalcones leading to formation of the epoxy-ketones 11a-j with good yields and enantiomeric excesses. The best results were obtained using the catalyst 2b. The developed methodology for epoxidation of enals was further employed in the synthesis of α-epoxy-aciloxycarboxamides through a one pot Tandem epoxidation/Passerini reaction. Compounds 15a-f are novel and had their activity evaluated from the inhibition of cathepsins K, V and L, showing interesting inhibitory percentages for two compounds. This methodology was also applied in the asymmetric synthesis of two stereoisomers of 3,4-epoxy-6,9-eneicosadiene (16), possible sex pheromone component of the moth Thyrinteina arnobia, a serious pest of eucalyptus and other native plants in Brazil.
Synthesis and application of organocatalysts in asymmetric epoxidation reactions aiming at the synthesis of bioactive compounds
Keywords: Síntese orgânica; Epoxidação; Organocatálise assimétrica; Compostos bioativos.; CIENCIAS EXATAS E DA TERRA::QUIMICA